Autophagy in Femoral Head Necrosis of Broilers Bone Metabolism Parameters and Autophagy-Related Gene Expression in Femoral Head Necrosis Induced by Glucocorticoid in Broilers - Pang, Kaiyi; Wang, Shujie; Li, Meng; Zhou, Zhenlei (Frontiers in Veterinary Science, 2021)
Objectives: In this study, the influence of methylprednisolone (MP) and 3-methyladenine (3-MA) on chondrocyte autophagy and bone quality were determined to investigate the mechanisms of femoral head necrosis in broilers. Methods: Chickens were divided into four groups: control, MP, 3-MA, and 3-MA+MP groups. Blood and bone samples were collected for biochemistry assay and bone quality determination. Cartilage was separated from the femoral head for histopathological analysis and gene expression detection. Results: The results indicated that MP treatment significantly affected blood levels of alkaline phosphatase, high-density lipoprotein, calcium, phosphorus, bone alkaline phosphatase, and osteocalcin in broilers. Additionally, MP treatment significantly increased blood levels of cholesterol, low-density lipoprotein, triglyceride, carboxy-terminal telopeptide of type-I collagen, and tartrate-resistant acid phosphatase 5. MP treatment also significantly decreased the levels of bone parameters compared with these values in controls, inhibited the expression of collagen-2 and aggrecan, and increased the expression of beclin1 and microtubule-associated protein 1 light chain 3 of the femoral head. Furthermore, following co-treatment with 3-MA and MP, 3-MA mitigated the effects of MP. Conclusions: Our findings demonstrated that autophagy may be involved in the pathogenesis of femoral head necrosis induced by MP in broilers, and this study provides new treatment and prevention ideas for femoral head necrosis caused by glucocorticoids.